BN nanoflake quantum-dot arrays: structural stability, and electronic and half-metallic properties. Issue 30 (20th July 2017) - Hu, R.; Zhang, Z. H.; Fan, Z. Q.
Abstract : One-dimensional arrays constructed by triangular h-BN nanoflakes are studied. It is found that the linking manner plays a crucial role in electronic and half-metallic properties and the traversed electric field further enhances half-metallicity. Abstract : New one-dimensional (1D) crystals, 1D quantum-dot arrays(1D QDAs), are proposed and constructed by an ordered arrangement of zigzag-edged triangular h-BN nanoflakes. Their geometrical stability is confirmed by the calculated binding energy, phonon dispersion and molecular dynamics simulation. These 1D QDAs demonstrate different quantum confinement effects on electronic and half-metallic properties due to different linking modes. For example, in the nonmagnetic state, different 1D QDAs are predicted to be semiconductors or metals remarkably depending on their linking manner, whereas in the ferromagnetic state, they are found to be all prominent half-metals but with greatly different gaps from ∼0.6 to 5.1 eV, reaching a difference almost as large as 10 times. In addition, the study on the electric–magnetic coupling effects suggests that the applied traversed electric field can significantly benefit the enhancement of 1D QDA half-metallicity by further enlarging the gap.